MARKETING STRATEGY TO INCREASE PURCHASE INTENTION; THE IMPACT OF INFLUENCER MARKETING ON PURCHASE INTENTION (The Indonesian Journal of Business Administration, 2021)
Indonesia’s leather industry has been one of the prominent sectors and is contributing significantly to the country’s economy, as Directorate General of National Export Development Ministry of Trade of The Republic of Indonesia, Leather industry in Indonesia is one of the biggest sectors which support Indonesian economy. Promotion in various ways, including influencer marketing as a relevant way of word of mouth for Architara leather goods has to boost its profitability as a newcomer in the industry. The technological advancement has enabled electronic word of mouth, in which this the result reveals that Attractiveness, Credibility, and Product Congruence influences purchase intention.The conceptual framework of this research is consistent with the analysis of internal and external environments of the business. Internal business analyse marketing mix and STP whereas external analysis observes PESTEL, competitor, as well as conduct a market research discussing influencer marketing. The influencer marketing are divided into variables; Attractiveness, Credibility, Product Congruence, and Purchase Intention.Keywords : Influencer Marketing, Attractiveness, Credibility, Product Congruence, Purchase Intention